Dilating and fracturing side struts of open cell stents frequently used in pediatric cardiac interventions—An in vitro study. (8th August 2018) - Krasemann, Thomas; Kruit, Marco N.; van der Mark, Arthur E.; Zeggelaar, Martijn; Dalinghaus, Michiel; van Beynum, Ingrid M.
Abstract : Background: Open cell stents are frequently used in interventional therapy of congenital heart disease. Overstenting of vessel branches may necessitate strut dilation. Methods and Results: The strut size achievable in Bard Valeo and Cook Formula stents, and the pressure necessary to fracture struts was assessed. In addition, a self expanding stent (Optimed SinusflexDS) was also tested. With the original balloon at nominal pressure, in Valeo stents side struts could be dilated to approximately 90% of the nominal stent diameter, in Formula stents to approximately 80%. With larger high pressure woven balloons, strut size increased to approximately 125% in Valeo stents, and to approximately 105% in the Formula. Strut fracture can connect two adjoining struts. Pressures were dependent on the balloon utilized. Sidestruts of the Sinusflex could lastingly overdilated with large balloons only. Conclusion: Dilation and overdilation of side struts in open cell stents can be achieved. Dependent on the clinical context, the original balloon used to place the premounted stent can be used to achieve strut dilation, but woven high pressure balloons maybe safer for patients. Should a larger diameter be required, these high pressure woven balloons can achieve bigger diameters and even strut fracture.